(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
TheHaryana Panchayati Raj Act, 1994 incorporated all the essential provisions ofthe 73rd Amendment Act. It has made the Gram Sabha a soul ofPanchayati Raj System. It provides a platform for the direct participation ofthe people. It is mandatory to hold at least two Gram Sabha meetings annually,one between 15 May to 15 June and the second from 15 November to 15 December.Section 11(2) of the Act provides that if the Sarpanch fails to hold twogeneral meetings on the dates fixed, he shall automatically cease to holdoffice from the date on which the second meeting was to be held.